A prototypic modified risk tobacco product exhibits reduced effects on chemotaxis and transendothelial migration of monocytes compared with a reference cigarette. (June 2015) - van der Toorn, Marco; Frentzel, Stefan; Goedertier, Didier; Peitsch, Manuel; Hoeng, Julia; De Leon, Hector
Highlights: CXCL12 and a functional monolayer of HCAECs are required for monocytes to differentiate and acquire an adhesive phenotype. Extracts from pMRTP induce less inflammation and migration and are less cytotoxic than those from reference tobacco products. Heating instead of burning tobacco reduces the number and amounts of constituents that are harmful to cardiovascular tissues. Abstract: Monocyte adhesion and migration to the subendothelial space represent critical steps in atherogenesis. Here, we investigated whether extracts from the aerosol of a prototypic modified risk tobacco product (pMRTP), based on heating rather than combusting tobacco, exhibited differential effects on the migratory behavior of monocytes compared with that from the reference cigarette, 3R4F. THP-1 cells, a monocytic cell line, and human coronary arterial endothelial cells (HCAECs) were used to investigate chemotaxis and transendothelial migration (TEM) of monocytes in conventional and impedance-based systems. THP-1 cells migrated through a monolayer of HCAECs in response to C-X-C motif ligand 12 (CXCL12), a chemokine involved in diverse cellular functions including chemotaxis and survival of stem cells. Treatment of THP-1 cells with extracts from 3R4F or pMRTP induced concentration-dependent increases in cytotoxicity (7-aminoactinomycin D), and inflammation (IL-8 and TNF-α). CXCL12-mediated chemotaxis and TEM were decreased in extract-treated THP-1 cells. Extracts from 3R4F were ~21 times more potent than those from pMRTP in all examined endpoints. Extracts from 3R4F and pMRTP induced concentration-dependent responses in assays of inflammation, cytotoxicity, chemotaxis, and TEM. Furthermore, our findings indicate that extracts from a pMRTP are significantly less cytotoxic and induce less inflammation than those from the reference cigarette, 3R4F.